Tyrosine kinase inhibitor resistance in pediatric chronic myeloid leukemia: a case report (Medical Journal of Indonesia, 2020)
Pediatric chronic myeloid leukemia (CML) is a hematopoietic malignancy, treated by tyrosine kinase inhibitor (TKI). Previously, imatinib resistance in CML was treated with nilotinib as a second line. However, in Indonesia, where the options of TKIs are limited, no case has been reported. We describe TKI-resistance of a pediatric CML case in Dharmais Cancer Hospital, Jakarta. A 17-year-old boy presented with loss of complete hematologic response after 4 years of imatinib treatment. Diagnosis of relapsed CML with blast crisis was confirmed, and nilotinib was given accordingly. He achieved hematological and optimal response after 2 weeks and 3 months of treatment, respectively. However, in the 12-month evaluation, he failed to achieve major molecular response and acquired the second resistance to TKI. Since imatinib resistance marks the poor prognosis, initial optimal response of nilotinib treatment remains inconclusive to predict the final outcome.